2021
DOI: 10.3390/plants10091899
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plasma Activated Water on Maize (Zea mays L.) under Arsenic Stress

Abstract: Plasma activated water (PAW) is a source of various chemical species useful for plant growth, development, and stress response. In the present study, PAW was generated by a transient spark discharge (TS) operated in ambient air and used on maize corns and seedlings in the 3 day paper rolls cultivation followed by 10 day hydroponics cultivation. For 3 day cultivation, two pre-treatments were established, “priming PAW” and “rolls PAW”, with corns imbibed for 6 h in the PAW and then watered daily by fresh water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Further on, Gierczik et al [ 12 ] studying the effect of PAW on the seeds germination and plants growth under stress conditions have found that the PAW, which contains significant H2O2 ${{\rm{H}}}_{2}{{\rm{O}}}_{2}$ besides nitrate and nitrite, improves the germination of barley under stress conditions and the stress tolerance of plants. Similar effects have been observed by Lukacova et al [ 20 ] in the case of maize under arsenic stress. The combined positive effect of H2O2 ${{\rm{H}}}_{2}{{\rm{O}}}_{2}$, nitrate and nitrite on plant growth has also been shown by Yemeli et al [ 21 ] in the case of maize and barley, while Laurita et al [ 22 ] have found that PAW enhances the defense mechanisms in grapevine plants and increases the plant fitness.…”
Section: Introductionsupporting
confidence: 89%
“…Further on, Gierczik et al [ 12 ] studying the effect of PAW on the seeds germination and plants growth under stress conditions have found that the PAW, which contains significant H2O2 ${{\rm{H}}}_{2}{{\rm{O}}}_{2}$ besides nitrate and nitrite, improves the germination of barley under stress conditions and the stress tolerance of plants. Similar effects have been observed by Lukacova et al [ 20 ] in the case of maize under arsenic stress. The combined positive effect of H2O2 ${{\rm{H}}}_{2}{{\rm{O}}}_{2}$, nitrate and nitrite on plant growth has also been shown by Yemeli et al [ 21 ] in the case of maize and barley, while Laurita et al [ 22 ] have found that PAW enhances the defense mechanisms in grapevine plants and increases the plant fitness.…”
Section: Introductionsupporting
confidence: 89%
“…The exposure of seeds to HVED causes seed surface modification which shortens the imbibition time and increases wettability leading to faster oxygen diffusion into the embryo [ 15 ]. HVED treatment creates plasma-activated water (PAW) rich in ROS and RNS particles which can also affect germination [ 48 ]. Moreover, the PAW creates a higher amount of hydrogen peroxide (H 2 O 2 ) and nitric oxides (NO), longer half-life molecules which may alter the phytohormone balance in the seeds and promote germination [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then the germination paper towels were placed in Bio-Oxygen Demand (BOD) incubator at 24 ℃ for 7 days. After the incubation, the seed germination and vigor index were calculated by using the following formula (Lukacova et al 2021).…”
Section: Evaluation Of Seed Germination and Vigor Indexmentioning
confidence: 99%